2015
DOI: 10.1016/j.ebiom.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Modulation of Gut Microbiota Contributes to Alleviation of Both Genetic and Simple Obesity in Children

Abstract: Gut microbiota has been implicated as a pivotal contributing factor in diet-related obesity; however, its role in development of disease phenotypes in human genetic obesity such as Prader–Willi syndrome (PWS) remains elusive. In this hospitalized intervention trial with PWS (n = 17) and simple obesity (n = 21) children, a diet rich in non-digestible carbohydrates induced significant weight loss and concomitant structural changes of the gut microbiota together with reduction of serum antigen load and alleviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
355
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(392 citation statements)
references
References 72 publications
16
355
2
Order By: Relevance
“…CIA allows each variable set to be analyzed by a different ordination algorithm (Dray et al , 2003a). Co-inertia analysis has been used in several recent studies to reveal relationships between human-associated microbiome and metabolome datasets in the gut of the elderly (Claesson et al , 2012), on the intestinal mucosal surface (McHardy et al , 2013), and in obese subjects (Zhang et al , 2015). …”
Section: Interpretive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIA allows each variable set to be analyzed by a different ordination algorithm (Dray et al , 2003a). Co-inertia analysis has been used in several recent studies to reveal relationships between human-associated microbiome and metabolome datasets in the gut of the elderly (Claesson et al , 2012), on the intestinal mucosal surface (McHardy et al , 2013), and in obese subjects (Zhang et al , 2015). …”
Section: Interpretive Methodsmentioning
confidence: 99%
“…Thus, it can also be used to assess if multiple ordination techniques applied to the same object-by-variable dataset produce similar results (Bassett et al , 2015). Other examples of PA use are provided in studies by (Claesson et al , 2012), (McHardy et al , 2013), and (Zhang et al , 2015). …”
Section: Interpretive Methodsmentioning
confidence: 99%
“…It was recently shown that the response to a probiotic mix may be modulated by the initial microbiota configuration, the latter driving the permissivity to fermented food lactic acid bacteria [106,107]. Similarly, work by Chung et al indicates that depending on the presence/absence of specific fiber degraders, the microbiota may be totally irresponsive to specific fibers [108].…”
Section: Microbiota As Target For Functional Modulation Functional Numentioning
confidence: 99%
“…In a clinical trial on nutritional intervention of genetically obese children with Prader- Willi syndrome, high complex carbohydrates in the diet induced significant changes of the gut microbiota with concomitant weight loss and alleviation of metabolic deteriorations (Zhang et al, 2015). NMR-based metabolomic analysis of the urine samples showed a significant decrease of TMAO concentration.…”
Section: The Multiorganismal Humanmentioning
confidence: 99%